2015
DOI: 10.5114/jcb.2015.52140
|View full text |Cite
|
Sign up to set email alerts
|

Original paper Efficacy and safety of electronic brachytherapy for superficial and nodular basal cell carcinoma

Abstract: PurposeSurface electronic brachytherapy (EBT) is an alternative radiotherapy solution to external beam electron radiotherapy and high-dose-rate radionuclide-based brachytherapy. In fact, it is also an alternative solution to surgery for a subgroup of patients. The objective of this work is to confirm the clinical efficacy, toxicity and cosmesis of a new EBT system, namely Esteya® in the treatment of nodular and superficial basal cell carcinoma (BCC).Material and methodsThis is a prospective single-center, non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 24 publications
5
23
0
Order By: Relevance
“…7 Gy per fraction given at the prescription depth (typically 3 mm) [34]. This is delivered twice weekly with a minimum interval of 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…7 Gy per fraction given at the prescription depth (typically 3 mm) [34]. This is delivered twice weekly with a minimum interval of 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is limited research on brachytherapy, some studies have shown that electronic brachytherapy (EBT), a type of contact radiotherapy, is an effective and safe option for superficial and nodular BCC. 6 In this study, the authors found that, even with tumor thickness averaging 4 mm, a complete response to EBT was documented in all lesions after 42 Gy divided in 6 fractions of 7 Gy. Moreover, only mild adverse events and good cosmetic outcomes were noted.…”
mentioning
confidence: 61%
“…Moreover, only mild adverse events and good cosmetic outcomes were noted. 6 The recurrence rate of radiotherapy is around 3.5%, comparable to surgical excision (3.8%), as well as to Mohs surgery (3.8%). 7 After EBT, our patient experienced a full resolution of a 2-mm thick BCC with minimal local erythema, which was demonstrated dermoscopically and histologically.…”
mentioning
confidence: 90%
“…A prospective, single-center, non-randomized study reported preliminary data for the treatment of BCC with the Esteya device [61]. Twenty patients with 23 lesions exhibited complete response with no recurrence at 6-month follow-up.…”
Section: New Technology: Electronic Brachytherapymentioning
confidence: 98%